2014
DOI: 10.2147/ppa.s66655
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of patients’ adherence with hypoglycemic medications among Papua New Guineans with type 2 diabetes: influencing factors

Abstract: PurposeThe aims of this study were to evaluate the extent of adherence to hypoglycemic medications, assess the relationship between adherence and glycemic control, and evaluate factors affecting adherence.Research design and methodsThis was a cross-sectional study of patients with established type 2 diabetes attending the Port Moresby General Hospital Diabetes Clinic. Face-to-face interviews were conducted using a questionnaire designed for the study and data were collected concerning the 3 months prior to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…A study in Australia showed that 59.6% of patients omitted their hypoglycemic drugs 3 months before the study interview. 4 Another study, in the US, found that overall adherence to oral medications for military veterans with diabetes ranged from 42.5% to 54.1%. 5 Since treatment regimens will not work effectively if medications are not taken as prescribed, it is essential to pinpoint the causes for poor medication adherence, as well as intervention approaches to ensure optimal adherence.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Australia showed that 59.6% of patients omitted their hypoglycemic drugs 3 months before the study interview. 4 Another study, in the US, found that overall adherence to oral medications for military veterans with diabetes ranged from 42.5% to 54.1%. 5 Since treatment regimens will not work effectively if medications are not taken as prescribed, it is essential to pinpoint the causes for poor medication adherence, as well as intervention approaches to ensure optimal adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Those who used herbal medicines for the treatment of their diabetes were 3.3 times more likely to be nonadherent to anti-diabetic medications, although this was insignificant. Many predictors of adherence have been reported including having taken medication for more than 3 years, availability of antidiabetic drugs, ever had diabetic education ( 16 ) and age >60 years ( 9 ). Several sociodemographic factors that significantly associated with poor adherence were age 45 years, non-European geographical origin, financial difficulties, and being professionally active.…”
Section: Discussionmentioning
confidence: 99%
“…Almobarak et al (2017) showed that the prevalence of diabetic foot in Sudan was around 18% ( 6 ), while retinopathy was reported to affect 78% of individuals with type 2 diabetes in Sudan ( 7 ). Importantly, several studies worldwide documented that the rates of adherence are suboptimal ( 8 - 13 ). Different factors have been associated with poor adherence including diabetes duration, inadequate patient education, side effects, the complexity of treatment regimen, unavailability of medicines, the high cost of medications, forgetfulness, and irregularity of follow-up ( 14 -17).…”
Section: Introductionmentioning
confidence: 99%
“…The adults with type 2 DM who were 100% (OR: 1.87, p = 0.0081) and those who were 90% (OR: 2.02, p = 0.0353) adherent to hypoglycaemic medications had a statistically significant risk of a high HbA1c of >10% (875.5 mmol/mol; Pihau-Tulo, Parsons, & Hughes, 2014). Therefore, the prescription of a combination therapy indicated more aggressive treatment of glycaemic control due to deterioration of the disease (Amarasekara, Fongkaew, Wimalasekera, Turale, & Chanprasit, 2015).…”
Section: Medication Usagementioning
confidence: 99%